Efektivitas Model Pembelajaran Cooperative Script Terhadap Kemampuan Pemahaman Konsep Matematis Peserta Didik - Sriyanti, A.; Risnawati; Munirah; Abrar, Andi Ika Prasasti (Department of Mathematics Education, 2024)
This study aims to describe the mathematical concept understanding ability of students who use and do not use the Cooperative Script learning model, find out the differences between the two, and measure the effectiveness of the model in class VIII SMPN 1 Salomekko. This study used a quantitative approach with an experimental design of Nonequivalent Control Group Design. The research samples were class VIII A as the experimental class (33 students) and class VIII B as the control class (32 students), which were selected through simple random sampling technique. The instrument used was a description question, with data analysis using descriptive statistics and Independent Sample T Test hypothesis testing. The results showed that the Cooperative Script model effectively improved students' mathematical concept understanding ability. In the experimental class, the average score increased from 22.03 to 55.82, while in the control class it increased from 21.03 to 46.19. In addition, there is a significant difference between the average ability of the two classes, which shows the effectiveness of the Cooperative Script model in learning mathematics.